Emerging Neuroplasticity-based Therapies in Stroke Rehabilitation: Literature Review - Selohandono, Andrianto; Zamroni; Budi Rahayu, Ana (Ahmad Dahlan Medical Journal, 2024)
Stroke is a significant global health concern, leading to substantial mortality and long-term disability among survivors. Traditionally, stroke rehabilitation has focused on compensatory strategies to mitigate the effects of impairments rather than addressing their root causes. However, growing recognition of the brain's capacity for neuroplasticity a process involving the brain's ability to reorganize itself in response to injury has prompted a paradigm shift. This review explores the mechanisms of neuroplasticity and the latest neuroplasticity-based interventions for stroke recovery. It highlights the role of neuronal regeneration, synaptic plasticity, and functional reorganization in promoting recovery. Additionally, the review discusses emerging therapies, such as Constraint-Induced Movement Therapy, mirror therapy, robot-assisted training, and non-invasive brain stimulation techniques, which have shown promise in enhancing neuroplasticity and improving functional outcomes. Although the results of these interventions have been complex and the effect sizes modest, they underscore the potential for innovative approaches to harness neuroplasticity in stroke rehabilitation.